MATHEMATICAL MODELING OF THE SYSTEM’S MOTION, THE STABILITY OF WHICH IS BEING STUDIED - Mullajonov Rustamjon Vokhobjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Mathematical modeling of the motion of dynamic or mechanical systems plays an important role in the stability of the system’s motion. The structure of its mathematical model is especially important when studying the stability of the motion of complex systems. Therefore, when creating a mathematical model of the motion of such systems, it is important to consider the study of the stability of the system’s motion in the future.